2021
DOI: 10.1080/07853890.2021.1937694
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis reveals the participation of IL4I1, ITGB7, and FUT7 in reshaping the TNBC immune microenvironment by targeting glycolysis

Abstract: Background: The overall response rate of immunotherapy in triple-negative breast cancer (TNBC) remains unsatisfactory. Accumulating evidence indicated that glucose metabolic reprogramming could modulate immunotherapy efficacy. However, transcriptomic evidence remains insufficient. Methods: Genes' relationship with glucose metabolism and TNBC-specific immune was demonstrated by weighted gene co-expression network analysis (WGCNA). The glucose metabolic capability was estimated by standardised uptake value (SUV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Integrin beta-7 has been suggested to play a role in high-risk multiple myeloma and overexpression of Integrin beta-7 has been associated with DNAhypomethylation [32]. In addition to its cell adhesion, migration and homing roles, Integrin beta-7 has also been suggested to participate in regulating the immune microenvironment as well as suppressing cell proliferation through the glycolysis/glucose metabolism pathway [33,34]. However, the exact role of Integrin beta-7 specifically in AML is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin beta-7 has been suggested to play a role in high-risk multiple myeloma and overexpression of Integrin beta-7 has been associated with DNAhypomethylation [32]. In addition to its cell adhesion, migration and homing roles, Integrin beta-7 has also been suggested to participate in regulating the immune microenvironment as well as suppressing cell proliferation through the glycolysis/glucose metabolism pathway [33,34]. However, the exact role of Integrin beta-7 specifically in AML is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has pointed out that instead of IDO1, interleukin 4 induced 1 (IL4I1) is the novel and the main Trp‐catabolic enzyme in glioma and chronic lymphocytic leukemia, which explains the major reason why the clinical trials of IDO1 inhibitors are a failure 16 . Previous studies have also shown that IL4I1 is a crucial player in the immunosuppressive TME, which promotes the progression of breast cancer, ovarian cancer, melanoma, and colon cancer 17–22 . IL4I1 acts as the main regulator of Trp/AHR signaling and promotes the immune evasion of several cancer types, underscoring its significance as a key drug target.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al. confirmed that FUT7, IL4I1, and ITGB7 could remodel the glucose metabolism to strengthen the immunotherapy effect ( 39 ). The pivotal glycan-binding proteins, including selectins, singles, and galectins, are important orchestrators in regulating the immune response in tumor metastasis ( 40 ).…”
Section: Discussionmentioning
confidence: 99%